Discussion about Voltage Fluctuation Limit in the National Power Quality Standard - ZHU Mingxing; DONG Ruian; QIAN Chenchen; PEI Yantao (Kongzhi Yu Xinxi Jishu)
Voltage fluctuation and flicker are the important factors of power quality. The relative national standard has been modified twice, but the provision of voltage fluctuation limit still exist ambiguities and shortcomings. It discussed the provision of voltage fluctuation limit based on GB 12326-2008 Power quality-Voltage fluctuation and flicker, and gave two different evaluation methods of voltage fluctuation. The difference between the two methods was studied through the actual test data of electric arc furnace, and scientific and reasonable voltage fluctuation limits and evaluation method were put forward.